Peningkatan Kompetensi dan Profesionalitas Warga Desa Tambaksawah Sidoarjo dalam Mengoperasikan Microsoft Excel Untuk Menuju Desa Yang Unggul dan Produktif - Sa'idah Zahrotul Jannah; Elly Pusporani; Elly Ana; Idrus Syahzaqi; Afifah Nur Makkiyah; Aulia Ramadhanti; Azizah Dewi Ariyani; Azzah Nazhifa Wina Ramadhani; Nadya Lovita Hana Trisa; Nashwa Carista; Sheila Sevira Asteriska Naura (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Tambaksawah Village, Sidoarjo, is an industrial village that has the potential to improve the quality of life. However, this village faces obstacles, such as the limited skills of village officials using Microsoft Excel and the minimal application of technology in village institutions. Community service programs using Microsoft Excel are useful in supporting village administration efficiency and encouraging productivity. The methods include on-site training, group mentoring, international certification, and certification exams. Training followed by mentoring is carried out for one month. The evaluation results show an increase in the average score from 50.4 to 60.16, which shows an increase the understanding of participants. Apart from 7 participants, only 5 participants succeeded in obtaining official certificates. This activity succeeded in improving participants' skills in operating Microsoft Excel, so it is hoped that this can be the first step to advancing technological capacity and can help in developing Tambaksawah Village.